(untitled) (Emancipação, 2026)
The article critically analyzes digitalization in Brazil’s social security system, particularly in social assistance, and its effects on vulnerable populations. Using an intersectional and decolonial approach, it discusses how technologies can expand access but also deepen inequalities when detached from territorial realities. Based on a comparison between Auxílio Brasil and the Cadastro Único, the study examines the limits and potential of digital transformation in the SUAS for guaranteeing rights. The action-research methodology included document analysis, open data, and socioterritorial assessment. The findings show that digital exclusion reinforces historical inequalities, while qualified data use can strengthen democratic processes when guided by social justice and participation. In this context, the Cadastro Único emerges as a strategic tool for promoting equity in SUAS socioterritorial management. i